Studi Kelayakan Pembangunan Hotel Sutan Raja Di Kota Kendari - Syamsuddin, Syamsuddin; Sunaryo, Sunaryo; Rachmat, La Ode Musa; Sufrianto, Sufrianto (Universitas Sulawesi Tenggara, 2020)
Hotels are one of the accommodation business entities that use part or all of their parts as lodging services, food and beverage service providers, and various other services for the general public which are managed by commercial means. Sutan Raja Hotel is one type of star hotel that will be built in Kendari city and it is hoped that this hotel can help improve the welfare of the people of Kendari City. Building a star hotel in a developing city like Kendari is not an easy matter, because in the construction of a hotel, it must also pay attention to the feasibility of building the hotel, both from the market, financial and technical aspects. The purpose of this research was to analyze the feasibility of developing Sutan Raja Hotel in Kendari City based on market, technical, and financial aspects. And to find out information and input to the owner whether the construction of Sutan Raja Hotel in Kendari City is feasible to be implemented in terms of market, technical, and financial aspects. The results of the technical aspects show that the construction of Sutan Raja Hotel in Kendari City is feasible, because it has a strategic location to carry out a business investment project for a hotel, with the distance around relatively close to the tourist attractions and other entertainment places. From the market aspect to get hotel rooms rented at star hotels in Kendari City, it is found that the number of hotel rooms to be rented at Sutan Raja Hotel Kendari City is 12,370 units per year and will increase by 200-300 units annually for 25 years of operation . The feasibility assessment of the project proposal was carried out an analysis, namely NPV was generated Rp. 320,941,000,000.00 (positive NPV) as desired, BCR obtained 2.55 greater than 1, IRR obtained 26.512% greater than the 12% commercial interest rate